A mixed ion-electron conducting network derived from a porous CoP film for stable lithium metal anodes. (7th June 2021) - Cao, Xin; Wang, Qian; Wang, Hangchao; Shang, Zhicheng; Qin, Jinli; Liu, Wen; Zhou, Henghui; Sun, Xiaoming
Abstract : CoP@Li||LFP showed superior cycle stability at high C-rates, showing the strength of the mixed ion-electron conducting host derived from porous CoP. Abstract : Rechargeable lithium metal batteries (LMBs) have been regarded as the most promising next-generation high-energy-density storage devices. However, the uncontrolled dendrite growth and short lifespan hinder their practical application, especially at high current densities. Herein, we propose a mixed ion-electron conducting scaffold derived from a porous CoP film with high surface area and lithiophilic properties, which serves as a host material for dendrite free lithium deposition. The scaffold is in situ transformed from the porous CoP film made by a facile electrodeposition process. In liquid electrolytes, the scaffold can not only reduce the lithium nucleation barrier but also ensure a uniform lithium-ion distribution, thereby achieving uniform and smooth lithium deposition. As a result, the Li||Cu cell shows a high coulombic efficiency (CE) of 98.63% for lithium plating/stripping, and the full cell with the LiFePO4 (LFP) cathode (Li||LFP) shows highly stable cycling performance at high C-rates, showing the strength of high ionic/electronic conductivity for stable lithium metal batteries.